Generación de una línea de Indumentaria urbana femenina a partir de la influencia de género musical reggaetón para la academia Magnanimos Complex Studio - Lagua Tomarima, Tatiana Anabel (2024)
Music, being a cultural link that unites people, provides identity and social cohesion. Within this project, the urban music phenomenon reggaeton is taken as an opportunity for clothing design aimed at connecting and collaborating with the passionate audience. The main impetus for this study lies in the marked acceptance that reggaeton has obtained among young audiences, which has sparked considerable interest in its cultural and social impact, particularly in the realm of dance. In this regard, specific issues were identified and addressed within the Magnanimos Complex Studio dance academy, aiming to understand how music, specifically reggaeton, It influences the clothing and stage expression of urban dancers. The methodology used was the review of information through bibliographic methods, data collection and analysis, synthesis information, and systematization of the clothing design method. The focus of this project revolves falls on the analysis of urban dancers and their stage clothing. The proposal of this study contributes to clothing with the fusion of distinctive elements of the reggaeton musical genre and carefully adapted to the technical requirements necessary for used during urban dance presentations.